Triple play plus German - Syracuse Language Systems (New York : Syracuse Language Systems, Inc., 1994)
Interactive games and conversations for language learning fun.
System requirements: IBM PC or compatible PC; 386SX33 or higher microprocessor; Windows 3.1 or 95 operating system; 4MB of RAM(8 MB recommended); 6MB of hard drive space; SVGA 256-colors display; CD-ROM drive; Sound card; Speaker or headphones; Mouse; Microphone (connected to the sound card)
Keywords: German language -- Study and teaching -- CD-ROMs.; German language -- Self-instruction.; CD-ROMs.